Integrated 'all-in-one' strategy to stabilize zinc anodes for high-performance zinc-ion batteries. Issue 3 (15th September 2021) - Li, Canpeng; Xie, Xuesong; Liu, Hui; Wang, Pinji; Deng, Canbin; Lu, Bingan; Zhou, Jiang; Liang, Shuquan
Abstract: Many optimization strategies have been employed to stabilize zinc anodes of zinc-ion batteries (ZIBs). Although these commonly used strategies can improve anode performance, they simultaneously induce specific issues. In this study, through the combination of structural design, interface modification, and electrolyte optimization, an 'all-in-one' (AIO) electrode was developed. Compared to the three-dimensional (3D) anode in routine liquid electrolytes, the new AIO electrode can greatly suppress gas evolution and the occurrence of side reactions induced by active water molecules, while retaining the merits of a 3D anode. Moreover, the integrated AIO strategy achieves a sufficient electrode/electrolyte interface contact area, so that the electrode can promote electron/ion transfer, and ensure a fast and complete redox reaction. As a result, it achieves excellent shelving-restoring ability (60 hours, four times) and 1200 cycles of long-term stability without apparent polarization. When paired with two common cathode materials used in ZIBs ( α -MnO2 and NH4 V4 O10 ), full batteries with the AIO electrode demonstrate high capacity and good stability. The strategy of the 'all-in-one' architectural design is enlightened to solve the issues of zinc anodes in advanced Zn-based batteries. Abstract : The integrated 'all-in-one' electrode combines the merits of structural design, interface modification and electrolyte optimization, which can effectively promote the reversibility and stability of zinc-based batteries.